Medieval Religious, Religions, Religion - Ames, Christine Caldwell (History compass, 2012)
This article sketches the most important shift in medieval religious history over the past few decades: the transition from "church history" to "the history of religious culture." First, it surveys the field’s expansion of "the religious" beyond a clerical elite to a broad demographic of the faithful, and its interest in devotion and lived experience in ways that have produced more nuanced appreciation of the varieties of Christian orthodoxy. Second, it sketches how the religions falling under the aegis of medieval religious history have increased from Latin Christianity only to Judaism, Islam, Greek Christianity, and even to forms of religiosity identified as pagan. Third, it argues that regardless of the field’s many expansions and changes, scholars have tended not to make explicit the definitions of "religion" with which they work, and considers the ramifications and possible value of doing so.